Analysis and System Design at Mitra Sejati Hospital for Patient Drug Administration using Data Mining and Apriori Algorithm - Manurung, Johanes Rico Alexander; Khairani, Mufida; Dharmawati, D (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
This research focuses on system analysis and design at Mitra Sejati Hospital to increase the efficiency of administering medicines to patients. In this effort, data mining approaches and Apriori algorithms were implemented to identify significant treatment patterns and facilitate better decision making in medication administration management. This research is aimed at finding out how to analyze data on drug administration to patients at Mitra Sejati Hospital. The research methodology includes the system requirements analysis stage, collecting patient treatment data, and identifying treatment patterns using data mining techniques. The Apriori algorithm is used to extract association rules that represent the relationship between drugs given to patients. Next, system design was carried out to integrate the analysis results into the drug administration process at Mitra Sejati Hospital. The research results show that the application of data mining and the Apriori algorithm can help identify critical treatment patterns, reduce the risk of drug interactions, and increase the efficiency of the drug administration process. The proposed system is able to provide more precise drug recommendations based on the patient's medication history. By combining data mining technology and the Apriori algorithm in the drug administration system, Mitra Sejati Hospital can optimize patient medication management, improve the quality of health services, and reduce the potential risk of errors in medication. This research contributes to the development of intelligent and innovative health information systems in the hospital environment.